STUDI KASUS GAP GENERASI DALAM PERSPEKTIF NILAI PERSONAL DAN BUDAYA ORGANISASI PADA PT. JASA RAHARJA (PERSERO) CABANG BALI - Yanuar Fauzuddin; Mochammad Syaiful Arif; Dwi Sasono; Hendrik Rizqiawan; Andi Iswoyo (Fakultas Ekonomi dan Bisnis Universitas Mataram, 2022)
This study aims to explore the phenomenon of the generation gap that occurs at PT. Jasa Raharja (Persero) Bali Branch from the perspective of personal values and organizational culture. The multiple-case study method was used to do this. Data were collected through a survey using instruments from the Rokeach Value Survey for personal values and the Organizational Culture Assessment Instrument (OCAI) for organizational culture. A total of 47 respondents involved are employees of PT. Jasa Raharja (Persero) Bali Branch. The results obtained indicate that there is no generation gap, because both generations X, Y, and Z have the same terminal and instrumental values. The organizational culture that is felt today and which is expected in the future also shows the same type, namely clan, and market culture.